Research on Energy Dissipation Laws of Coal Crushing under the Impact Loads - Dengke Xu; Chaomin Mu; Wenqing Zhang; Zhongqing Li (Shock and Vibration)
Dynamic crushing characteristics of coals are closely related with energy absorption and release of coals under certain strain rate. Hence, it is necessary to investigate energy dissipation laws of coal crushing under the impact loads with different strain rates. Based on the dynamic and static mechanical tests, crushing energy, total absorption energy, total releasable elastic latent energy, and relations between fractal feature of fragments, mean particle diameter and energy during crushing behaviors of outburst coal and nonoutburst coal were investigated. According to research results, crushing energy, total absorption energy, and releasable elastic latent energy of outburst coal and nonoutburst coal are related with strain rate, and they present exponential growths with the increase of the strain rate. However, the energy dissipation rate (ratio of crushing energy and incident energy) was basically constant at about 10%∼20%, that is, energy dissipation rate is a variable unrelated with strain rate. There is a good logarithmic relationship between the dynamic compressive strength of coals and the absorption energy density and elastic latent energy density, and dynamic comprehensive strength of coals has important impacts on energy absorption. The fractal features of coal fragments were obvious under dynamic impacts. The higher fractal dimension of fragment and the smaller mean particle diameter of experimental fragments bring the greater energy needed.